Quality of life related to oral health in higher education students - Gomes,Maria José (2022)
Abstract Introduction: Oral health-related quality of life is multidimensional and reflects the impact of oral health (OH) on functional, social and psychological well-being. Oral health behaviors translate throughout the life cycle and can affect the quality of life. Objective: To assess oral health-related quality of life in higher education students; to infer the relationship between sociodemographic and behavioral variables and the level of self-reported oral health-related quality of life. Methods: Cross-sectional, quantitative, descriptive and correlational study in 430 higher education students from the northen region of portugal. Predominance of female individuals (n=342; 79.5%) aged between 18 and 22 years (n=297; 69.1%). An online survey consisting of sociodemographic and behavioral variables and the short version of the Oral Health Impact Profile (OHIP-14) was applied. Nonparametric tests with a 95% confidence interval were used. Results: Most students brush their teeth and mouth two or more times a day (n=367; 85.4%) and have oral cavity pathology (n=306; 71.1%). 50.2% (n=216) have edentulous areas and 42.3% (n=188) attend consultations with OH professionals only when absolutely necessary. The average OHIP-14 score was 6,142 (±9,137). There is a statistically significant association between behavioral variables and the total OHIP-14 score. Conclusion: The average OHIP-14 score reflects the absence of an impact of oral health on the sample's quality of life. Oral health behaviors influence oral health-related quality of life.